Relatives Experience More Psychological Distress Due to COVID-19 Pandemic-Related Visitation Restrictions Than In-Patients - Felser, Sabine; Sewtz, Corinna; Kriesen, Ursula; Kragl, Brigitte; Hamann, Till; Bock, Felix; Strüder, Daniel Fabian; Schafmayer, Clemens; Dräger, Désirée-Louise; Junghanss, Christian (Frontiers in Public Health, 2022)
Background: The COVID-19 pandemic led to visiting restrictions (VR) of patients in hospitals. Social contacts between patients-relatives play an important role in convalescence. Isolation may cause new psychological comorbidity. The present study investigated the psychological distress of VR in inpatients and their relatives. Methods: From 01.04. to 20.05.2020, 313 inpatients (≥14 years) of the University Medical Center Rostock were interviewed by questionnaires and 51 relatives by phone. Subjective psychological distress was assessed by distress thermometer (0 (not at all) - 100 (extreme)). The study also investigated stressors due to VR , psychological distress in dependence of demographic or disease-related data, currently used communication channels and desired alternatives and support. Results: Relatives were more psychologically distressed by VR than inpatients (59 ± 34 vs. 38 ± 30, p = .002). Loss of direct physical contact and facial expressions/gestures resulted in the most distress. Psychological distress due to VR was independent of demographics and indicates small positive correlations with the severity of physical restriction and the general psychological distress of inpatients. The most frequent ways of communication were via phone and social media. Frequently requested alternatives for patients were other interlocutors and free phone/tablet use, for relatives visiting rooms with partitions. Conclusion: VRs are a stressor for patients and their relatives. The establishment of visiting rooms with partitions and the free use of phones/tablets could reduce the additional distress.